Design of triple-mode ring resonator for wideband microstrip bandpass filters - Srisathit, Kunnthphong; Worapishet, Apisak; Surakampontorn, Wanlop (My University, 2010)
A triple-mode microstrip ring resonator core for the design of bandpass filters is proposed in this paper. It is a modification of the conventional single-mode ring resonator with a pair of open-ended coupled lines and a shunt open stub for a transmission-line path of the ring substituted to form a triple-mode resonator. Since the triple-mode resonator possesses three resonances, one at the center frequency and the other two near the edges of the passband, a flat passband response can be achieved when it is employed to implement a bandpass filter. The resonator also exhibits attenuation poles close to the edges of the passband, thereby offering sharp rejection in the bandpass filter response. Moreover, since the signal applied at the input port is effectively forced to travel mainly through the transmission line path over the passband frequency, the loss incurred by the coupled lines is minimized. Extensive theoretical analysis of the triple-mode ring and design example of the bandpass filter prototypes based on the ring structure are given. The prototype filters's performance is validated through both simulations and experiments, where good agreement with the theoretical prediction is observed. © 2006 IEEE.
Keywords: Bandpass filter; harmonic suppression; ring resonator; sharp rejection; triple-mode; wideband response